Socketed Axes of the Irish Late Bronze Age: Understanding the Internal Rib Phenomenon - Terry Runner (EXARC Journal)
This study explores the possibility that the internal rib commonly recognised inside bronze socketed axes may suggest an entirely different step in the casting process than previously thought. The internal rib, more commonly referred to as a ‘hafting rib’, has always been regarded as a functional addition to help tighten the grip of the haft once fitted into the socket. However, many of the internal ribs inside bronze socketed axes produced in Ireland do not appear to optimize this function and in some cases contradict this implied intention all together. This study demonstrates that there are recognizable trends in their form that indicate a replicated step in the casting process and further suggests that the rib may be the signature focus for a procedure closely related to a casting technique.